NBN International (NBNi). (Bookseller)
The article focuses on NBN International (NBNi), a book distribution company in Plymouth, England. According to the article, the company operates a system of key account agents to work closely with publishers, and to provide the flexibility to service the individual business requirements of each different publisher client. It states that the company's Oracle-based information technology (IT) system provides great adaptability and they are constantly developing ways to interface with customers, publisher clients and other supply chain businesses.